A homoleptic, all-alkynyl-stabilized highly luminescent Au8Ag8 cluster with a single crystal X-ray structure. Issue 32 (27th July 2016) - Zhang, Rui; Zhao, Chongyang; Li, Xiumin; Zhang, Zongyao; Ai, Xicheng; Chen, Hui; Cao, Rui
Abstract : An all-alkynyl-stabilized, intensely luminescent Au–Ag cluster was synthesized and characterized with a very high solution quantum yield at room temperature. Abstract : A homoleptic, all-alkynyl-stabilized [Au8 Ag8 (ArCC)16 ] (1, Ar = 3, 5-di- tert -butylphenyl) cluster was synthesized and characterized with a single crystal X-ray structure. Reactions of 3, 5-di- tert -butyl-phenylacetylene with Ag(i ) and Au(i ) gave [Ag(ArCC)] n and Au(PPh3 )(ArCC), respectively, where both have unusually high solubility in nonpolar organic solvents. In addition to drastically increased solubility, the two bulky tert -butyl substituents on the phenyl ring can confine the metal core to a certain size by preventing infinite aggregation of d 10 metals. This feature makes the isolation of an all-alkynyl-stabilized Au–Ag cluster possible. Complex1 is intensely luminescent with a very high quantum yield of 0.67 in solution at room temperature. Theoretical studies offered valuable insights into the intriguing photophysical properties, and revealed the significant role of metal–alkynyl bond interactions and enhanced molecular rigidity provided by tert -butyl groups.